Integrating geology into archaeology: the water supply of Piraeus in Antiquity - Chiotis, E.D. (Journal of Greek Archaeology, 2019)
The peninsula of Piraeus is composed of the Mounichia Hill and the rocky Akti, connected through the NE-SW trending isthmus between the Kantharos and Zea harbors (Figure 1a). The great geomorphological advantage of the peninsula is its natural and safe harbors – Kantharos with the innermost Kophos Port, Zea and Mounichia – at a reasonable distance of eight kilometers from Athens.